1977
DOI: 10.1111/j.1476-5381.1977.tb07516.x
|View full text |Cite
|
Sign up to set email alerts
|

SOME OBSERVATIONS ON THE ANORECTIC ACTIVITY OF PROSTAGLANDIN F

Abstract: I Intracerebroventricular injection of prostanglandin F2a (10-40 jg) decreases food intake in a dosedependent manner in rats trained to consume their daily total food intake in a 2 h period. 2 This anorexia is also observed in satiated rats, which had ad libitum access to food. 3 The anorectic activity of prostaglandin F2a is not modified by changes in the internal environment of the body after food intake, such as increased blood glucose and insulin levels and decreased fatty acid levels, or by the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This is somewhat surprising considering that PGD 2 has been reported to stimulate appetite . Of the prostaglandins that have been reported to have anorexigenic properties (PGE 1 , PGF 1α , PGF 2α , PGA 1 , and PGB 1 ; , PGF 2α appears the most studied (Doggett and Jawaharlal, 1977;. However, two observations argue against a role for PGF 2α in cancer-induced anorexia.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This is somewhat surprising considering that PGD 2 has been reported to stimulate appetite . Of the prostaglandins that have been reported to have anorexigenic properties (PGE 1 , PGF 1α , PGF 2α , PGA 1 , and PGB 1 ; , PGF 2α appears the most studied (Doggett and Jawaharlal, 1977;. However, two observations argue against a role for PGF 2α in cancer-induced anorexia.…”
Section: Discussionmentioning
confidence: 58%
“…However, two observations argue against a role for PGF 2α in cancer-induced anorexia. Firstly, the appetite suppressing effect of PGF 2α is short-lived (possibly lasting ~ 180 min), especially when delivered peripherally (15-30 min; (Doggett and Jawaharlal, 1977), and, secondly, PGF 2α activates muscle protein synthesis , which is quite different to the muscle wasting that is characteristic for cachexia. sham-implanted mice.…”
Section: Discussionmentioning
confidence: 99%
“…intragastric. Furthermore, induction of similar pain with acetic acid does not affect food intake (Doggett & Jawaharlal, 1977). Since these fatty acids do not cause pyrexia an elevation of body temperature can also be excluded as a cause of anorexia.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first report (Horton, 1964), their possible involvement in the regulation of the hunger-satiety phenomenon has been studied by a number of workers (for references see Doggett & Jawaharlal, 1977). It has been shown that in man, fasting is associated with lower prostaglandin levels in the blood as compared with post-prandial samples (Greaves, McDonaldGibson & McDonald-Gibson, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The answer to this is not obvious, since the prostanoids reported to have anorexigenic properties are not that well characterized. The prostanoid that is the best characterized in regard to its anorexigenic properties is PGF2α [191,192]. However, the anorexigenic properties of PGF2α are short lived [192], and this prostanoid has also been shown to be involved in muscle anabolism [193], which is in sharp contrast to the muscle wasting seen during cachexic disease states.…”
Section: The Onset Of Cancer-induced Anorexia Is Cox-1 Dependent But mentioning
confidence: 89%